2015
DOI: 10.2147/ijn.s82788
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded colloidal carrier system: formulation optimization, mechanistic insight, ex vivo and in vivo evaluation

Abstract: The present work investigated the topical delivery potential of nanoemulsion gel loaded with curcumin (CR). CR nanoemulsion (CR-NE) was prepared by spontaneous emulsification method using oil (Labrafac PG/glyceryl triacetate), surfactant:cosurfactant (S mix ) (tween 80/polyethylene glycol [PEG] 400) and water. The pseudo-ternary phase diagrams were constructed and thermodynamic stability testing was performed. Droplet size and zeta potential were evaluated using photon correlation spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…The areas were then covered with gauze and an adhesive plaster. 17 An electric razor was used to clip the hair from the abdomen of the guinea pigs. The clipped areas were examined the next day, and guinea pigs with intact skin were chosen for the tests.…”
Section: Draize Skin Irritation Testmentioning
confidence: 99%
“…The areas were then covered with gauze and an adhesive plaster. 17 An electric razor was used to clip the hair from the abdomen of the guinea pigs. The clipped areas were examined the next day, and guinea pigs with intact skin were chosen for the tests.…”
Section: Draize Skin Irritation Testmentioning
confidence: 99%
“…The aforementioned products prevent skin aging due to oxidative stress and premature aging. [69][70][71][72][73] The combination of polyphenols with retinols enhances skin protection. Other than nanosizing, few delivery systems have been used to develop nanoantiaging creams and lotions for the enhanced activity of bioactive compounds to deeper layers of skin.…”
Section: Phytoconstituent-based Nanocosmeceuticals For Skin Therapy Nmentioning
confidence: 99%
“…Various nanodelivery techniques used in the formulation of cosmeceuticals are of solid lipid nanoparticles, nanostructured lipid carriers, liposomes, phytosomes, nanoemulsions, nanoniosomes, nanocapsules, and nanolipospheres. 4,57,70 Solid lipid nanoparticle-loaded resveratrol showed enhanced permeation in the porcine skin. 127 Similarly, colloidal silica emulsion loaded with quercetin also showed enhanced human skin permeation owing to the nanosizing of the compounds.…”
mentioning
confidence: 99%
“…In another study, curcumin loaded into nanoemulsion gel has shown fourfold higher skin permeation as compared to the curcumin solution in oil. Furthermore, antiarthritic evaluation on Freund's complete adjuvant‐induced arthritic rat model after application of curcumin nanogel in Wistar rats showed substantial removal of arthritic symptoms with enhanced topical availability at the site of application . Likewise, thymoquinone has several limitations which restrict its clinical applications.…”
Section: Scope Of Herbal Nano/submicromedicine In Rheumatoid Arthritimentioning
confidence: 99%
“…Furthermore, antiarthritic evaluation on Freund's complete adjuvant-induced arthritic rat model after application of curcumin nanogel in Wistar rats showed substantial removal of arthritic symptoms with enhanced topical availability at the site of application. [83] Likewise, thymoquinone has several limitations which restrict its clinical applications. Polymeric nanoparticles have been developed with the help of poly(lactide-co-glycolide) (PLGA) with 97.5% entrapment efficiency revealed higher potency as compared to thymoquinone alone.…”
Section: Scope Of Herbal Nano/ Submicromedicine In Rheumatoid Arthritmentioning
confidence: 99%